2013
DOI: 10.7567/jjap.52.110202
|View full text |Cite
|
Sign up to set email alerts
|

Steep Increase in Substrate Current in Metal–Oxide–Semiconductor Field-Effect Transistor with Multiple-Gate Configuration

Abstract: A steep increase in substrate current has been observed in a metal–oxide–semiconductor field-effect transistor with a multiple-gate configuration. Regarding gate voltage dependence, the substrate current plotted on a logarithmic scale exhibited a sharp rise with a slope of 6 mV/decade, which is 20 times steeper than that simultaneously measured for the drain current. Since the slope is even 10 times steeper than the ideal subthreshold swing of 60 mV/decade, the upsurge has been discussed using a hypothetical m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
6
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…The author has proposed a new type of oscillator in his previous study, 6) in which a device based on metal-oxidesemiconductor field-effect transistor (MOSFET) with a multiple-gate configuration was fabricated using a typical CMOS process, and a sharp resonance with a quality factor 7,8) of Q > 1500 was preliminarily observed at 300 MHz in the frequency dependence of the impedance measured for the backgate terminal of the device. 6) In another study, 9) commonly detected from the backgate terminal, a steep increase in the substrate current I sub was observed in the gate voltage (V gs ) dependence measured for a device fabricated with a similar device configuration using the same CMOS process. The upsurge in I sub was observed in a limited narrow range of V gs between the threshold voltage V th and the saturation voltage V sat = V ds + V th , where V ds is the drain bias voltage.…”
mentioning
confidence: 90%
See 4 more Smart Citations
“…The author has proposed a new type of oscillator in his previous study, 6) in which a device based on metal-oxidesemiconductor field-effect transistor (MOSFET) with a multiple-gate configuration was fabricated using a typical CMOS process, and a sharp resonance with a quality factor 7,8) of Q > 1500 was preliminarily observed at 300 MHz in the frequency dependence of the impedance measured for the backgate terminal of the device. 6) In another study, 9) commonly detected from the backgate terminal, a steep increase in the substrate current I sub was observed in the gate voltage (V gs ) dependence measured for a device fabricated with a similar device configuration using the same CMOS process. The upsurge in I sub was observed in a limited narrow range of V gs between the threshold voltage V th and the saturation voltage V sat = V ds + V th , where V ds is the drain bias voltage.…”
mentioning
confidence: 90%
“…Since the drain current I d simultaneously measured with I sub did not show any remarkable anomalies under a specific bias condition, it was suggested that the upsurge in I sub is caused by an increase in the impact ionization rate ¡, not in I d . 9) From the experimental results, it is reasonable to expect that a sharp resonance would also be observed only under a specific range of bias condition. 10) To confirm this expectation, the relationship between the bias condition and the sharp resonance was investigated in this study.…”
mentioning
confidence: 91%
See 3 more Smart Citations